(untitled) (Academia Journal of Medicine, 2018)
Background: One of the major causes of morbidity and mortality worldwide is acute myocardial infarction (AMI). Various cardiac markers have been used from time to time for assessing the diagnosis and prognosis of the disease. Hence; we planned the present study to evaluation of cardiac markers in patients with myocardial infarction. Subjects and Methods: The present study included assessment of different cardiac markers in patients with myocardial infarction. For the present study, ethical approval was obtained from the ethical committee of the institution, and written consent was obtained after explaining in detail the entire research protocol. A total of 20 AMI patient and 20 healthy controls were included in the present study. Fresh blood samples were taken and mean serum creatine kinase (CK), and cardiac troponin (CT) values were assessed and compared. All the results were analysed by SPSS software. Chi- square test was used for assessment of level of significance. Results: Mean value of CK-MB among the patients of the AMI group and the control group was 28 IU/L and 18 IU/L respectively. Mean value of CT among the patients of the AMI group and the control group was 4.8 ng/L and 0.5ng/L respectively. The cardiac biomarkers were found to be significantly raised among the AMI patients in comparison to the healthy controls. Conclusion: These biomarkers are assessable biological variables which function as indices for health analysis.